INDOLEBUTYRIC ACID AND ZINC IN THE ROOTING OF ROOTSTOCK SEEDLINGS OF ‘CRAVO’ LEMON TREES IN HYDROPONICS - Gomes, Wiara de Assis; Chalfun, Nilton Nagib Jorge; Faquim, Valdemar; Peche, Pedro Maranha; Soares Filho, Walter dos Santos (Revista de Ciências da Saúde Nova Esperança, 2020)
It was intended to evaluate the influence of indolebutyric acid (IBA) and zinc upon the rooting and development of rootstock of ‘Cravo’ lemon tree transplants of bare root to the modified hydroponic system in the grafting stage. Plants of rootstocks were treated by immersion of their root system into the different solutions tested for 24 hours. The experiment was arranged in a completely randomized design with seven treatments composed of IBA doses of 50, 100 and 200 mg.L-1 and Enervig® which contains in its formulation 33.92 g.L-1 of Zn at 60, 90 and 120 ml.L-1, and distilled water as a control with three replications and nine plants per plot, amounting to 189 plants , 15 cm tall. The rootstocks were transplanted to the tubes and taken to the modified hydroponic system, being evaluated (1) the development of the plants and (2) the time needed for the rootstocks to reach the grafting stage, considered ideal between 5 and 6 mm in diameter. The treatment with a solution of 100 mg.L-1of IBA proved superior to the others in the development of height and biomass yield and tended to provide greater stem diameter development. The grafting point was obtained, on average at 70 days after transplanting and the production of Rangpur lime trees in a hydroponic system may be recommended. When the root system of the ‘Cravo’ lemon tree was treated with 100 mg.L-1 solution the IBA grafting point was obtained at 45 days after transplanting.